2007
DOI: 10.4161/cc.6.17.4593
|View full text |Cite
|
Sign up to set email alerts
|

Neural Potential of a Stem Cell Population in the Hair Follicle

Abstract: The bulge region of the hair follicle serves as a repository for epithelial stem cells that can regenerate the follicle in each hair growth cycle and contribute to epidermis regeneration upon injury. Here we describe a population of multipotential stem cells in the hair follicle bulge region; these cells can be identified by fluorescence in transgenic nestin-GFP mice. The morphological features of these cells suggest that they maintain close associations with each other and with the surrounding niche. Upon exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 47 publications
7
63
1
Order By: Relevance
“…All Nestin-GFP cells isolated from either the adrenal medulla or cortex were included in spheres when cultured under low-attachment conditions, which is equivalent to what has been observed with Nestin-GFP cells from this mouse model in other tissues (Birbrair et al, 2011;Day et al, 2007;El-Helou et al, 2013;Li et al, 2003;Mignone et al, 2004;Mignone et al, 2007).…”
supporting
confidence: 58%
“…All Nestin-GFP cells isolated from either the adrenal medulla or cortex were included in spheres when cultured under low-attachment conditions, which is equivalent to what has been observed with Nestin-GFP cells from this mouse model in other tissues (Birbrair et al, 2011;Day et al, 2007;El-Helou et al, 2013;Li et al, 2003;Mignone et al, 2004;Mignone et al, 2007).…”
supporting
confidence: 58%
“…In fact, nestin did not appear to be a specific marker for stromal cells, as we observed that nestin expression spans many types of tissues, both mature and immature, in bone marrow and other tissues (SI Appendix, Fig. S12) (38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 83%
“…Transgenic mice carrying GFP under the control of the nestin promoter (ND-GFP 1,17 ) were used as a source of nestin-expressing hair follicle stem cells. All animal experiments were conducted according to the Guidelines for Animal Experimentation at Kitasato University.…”
Section: Methodsmentioning
confidence: 99%
“…They can be readily expanded in culture after isolation from the patient's hair follicle. Amoh et al, 8,11 Liu et al, 6 Mignone et al 17 and Sieber-Blum et al 2 have shown that nestin-expressing cells of the mouse hair follicle are multipotent. Yu et al 13,14 and Amoh et al 8,11 have shown that nestin-expressing cells of the human hair follicle are multipotent, suggesting their clinical potential.…”
Section: 11mentioning
confidence: 99%